Temporal disorientation during war: associations with work-family conflict, emotional distress, and burnout - Diamant, Irene; Kalfon Hakhmigari, Maor (Frontiers in Psychology, 2025)
IntroductionDisruptions in the temporal experience—such as subjective sense of time being long, short or distant compared to “objective” time—have been found in the context of extreme emotional events. This research, conducted a month after the start of the war in Israel, aimed to identify characteristics of temporal experience among a population facing ongoing crisis conditions, and to examine their relationship to emotional distress and burnout. Based on Hobfoll's Conservation of Resources Theory it was hypothesized that temporal disorientation is essentially the loss of a vital psychological-functional resource, and its intensity would be related to emotional distress and burnout during the war period.MethodsThe study involved 374 participants, recruited using a snowball sampling technique. They completed an online survey aimed at quantifying Temporal Disorientation, Burnout, Psychological Distress and Work-Family Conflict. Principal Component Analysis (PCA) was used to validate the factor structure of the Hebrew version of Temporal Disorientation questionnaire, Pearson correlation coefficient was used to evaluated correlations among the study variables; Hierarchical linear regression was used to model the outcome variables, emotional distress and burnout.ResultsTemporal confusion and difficulties in future orientation during wartime were significantly associated with emotional distress. The findings also indicate that temporal confusion and difficulties in future orientation were related to a loss of balance in the boundaries between major life roles, work-family conflict, and the development of occupational burnout.DiscussionThis study contributes an occupational angle to the existing literature on psychological reactions to prolonged crises. Understanding the role of temporal experience during a prolonged crisis can significantly contribute to intervention and prevention measures in the context of the development of mental pathology. Practical implications and study limitations are discussed.